2017
DOI: 10.1111/1462-2920.13725
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomics reveals signature metabolisms of exponentially growing and stationary phase marine bacteria

Abstract: SummaryMuch of the phenotype of a microorganism consists of its repertoire of metabolisms and how and when its proteins are deployed under different growth conditions. Hence, analyses of protein expression could provide important understanding of how bacteria adapt to different environmental settings. To characterize the flexibility of proteomes of marine bacteria, we investigated protein profiles of three important marine bacterial lineages -Oceanospirillaceae (Neptuniibacter caesariensis strain MED92), Roseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 68 publications
2
23
0
1
Order By: Relevance
“…This suggests that T. roseum uses CO to supplement available organic carbon during growth (mixotrophy) and persistence. These findings are broadly similar to observations made in other phyla, notably Actinobacteria and Proteobacteria, that hydrogenase and carbon monoxide dehydrogenase expression are induced by organic carbon limitation [28, 31, 6064].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests that T. roseum uses CO to supplement available organic carbon during growth (mixotrophy) and persistence. These findings are broadly similar to observations made in other phyla, notably Actinobacteria and Proteobacteria, that hydrogenase and carbon monoxide dehydrogenase expression are induced by organic carbon limitation [28, 31, 6064].…”
Section: Resultssupporting
confidence: 89%
“…Indeed, various heterotrophic bacteria have previously been inferred to be capable of oxidising atmospheric CO, including Proteobacteria [8083], Actinobacteria [84, 85], and a Thermogemmatispora strain [12]. Moreover, other datasets have shown that carbon monoxide dehydrogenase expression is activated during nutrient limitation in other aerobic organisms [6064]. However, in contrast to atmospheric H 2 [29, 32], it remains to be validated through genetic and biochemical studies that atmospheric CO oxidation can enhance survival of bacteria during persistence.…”
Section: Resultsmentioning
confidence: 99%
“…4). Carbohydrate metabolism was one of the most abundantly represented categories and has a key role in cell growth [42]. Expression of genes involved in most of the important steps in glycolysis was detected, and the expression of several glycolysis genes increased significantly in all three sediment samples during enrichment culturing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another way to enhance acetyl-CoA production was using the oxidative decarboxylation of pyruvate, which is generated from glycolysis, and the expression of genes related to the pyruvate dehydrogenase system was also significantly upregulated in the first stage (5 days) of enrichment. Acetyl-CoA is a molecule that participates in many biochemical reactions in protein, carbohydrate, and lipid metabolisms [42]. Its main function is to deliver the acetyl group to the TCA cycle to be oxidized for energy production.…”
Section: Resultsmentioning
confidence: 99%
“…Assignment of protein functions to taxonomic groups is crucial when analyzing metabolic processes in microbial communities, since thousands of taxa contribute proteins with overlapping functions in an environmental sample. Increased abundance of some functions may thus be accompanied by decreased abundance of others in the same category, as shown to occur during exponential and stationary growth phases (34). We focused on the most abundant bacterial taxa to identify the metabolic particularities of organisms in P3 versus P2 (Fig.…”
Section: Discussionmentioning
confidence: 99%